2021
DOI: 10.3390/polym13020232
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Evaluation for the Removal of Nickel, Mercury, and Barium Ions from Single-Component and Mixtures of Aqueous Solutions by Using an Optimized Biobased Chitosan Derivative

Abstract: In this experimental study, the use of 5-hydroxymethyl-furfural (HMF) organic compound as a grafting agent to chitosan natural polymer (CS) was examined. One optimized chitosan derivative was synthesized, and then tested (CS-HMF), in order to uptake nickel, mercury, and barium metal ions from single- and triple-component (multi-component) aqueous solutions. The characterization of the material before and after the metal uptake was achieved by scanning electron microscopy (SEM). The ability of the adsorption of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…e flask was magnetically stirred for 3 hours, and the content was filtered into a dry conical flask. en, 10 mL of the filtrate was titrated against sodium thiosulphate solution (5 × 10 −3 M) (Na 2 S 2 O 3 from Acros organics at 99% purity) using starch as indicator until a clear solution was observed according to equation (5). e volume delivered by the burette was then noted (V n ).…”
Section: Determination Of Iodinementioning
confidence: 99%
See 1 more Smart Citation
“…e flask was magnetically stirred for 3 hours, and the content was filtered into a dry conical flask. en, 10 mL of the filtrate was titrated against sodium thiosulphate solution (5 × 10 −3 M) (Na 2 S 2 O 3 from Acros organics at 99% purity) using starch as indicator until a clear solution was observed according to equation (5). e volume delivered by the burette was then noted (V n ).…”
Section: Determination Of Iodinementioning
confidence: 99%
“…Above permissible concentrations (toxic limits) of nickel of 0.1 mg/m 3 (World Health Organization (WHO)) [4], different types of diseases may be contracted such as lung cancer, renal edema, dermatitis, and gastrointestinal disorder. Conventional methods for nickel(II) removal from wastewater include chemical oxidation or reduction, chemical precipitation, ion exchange, membrane separation, filtration, electrochemical treatment, and adsorption [5]. ese techniques which are economically expensive suffer from incomplete metal removal, generation of toxic sludge, and other disposable waste products [6].…”
Section: Introductionmentioning
confidence: 99%
“…This means that the pseudo 2nd order model is more suitable to describe the adsorption mechanism of Cr(VI) ions on the surface of ppy/NC nanocomposite. These results indicated that the chemical sorption is the essential mechanism of Cr(VI) removal on the surface of ppy/NC nanocomposite rather than a usual mass transport [42,43]. Additionally, several previous works on the adsorption of Cr(VI) ions showed the applicability of pseudo 2nd order as a better model for the description of the removal mechanism than other kinetic models [44][45][46][47].…”
Section: Adsorption Kineticsmentioning
confidence: 79%
“…In this study, experiments related to contact time (5,15,30,45,60,90,120,150, and 180 min) in adsorption kinetic studies were performed by adding 0.1 g/L of synthesized adsorbent with 50 mL of dye solution. Then samples were shaken with agitation rate of 150 rpm, at pH = 2 and temperature of 25…”
Section: Adsorption Experimentsmentioning
confidence: 99%